1993
DOI: 10.1902/jop.1993.64.10.984
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Induced Peri‐Implantitis in the Micro Pig: Clinical and Histological Analysis

Abstract: The purpose of this pilot study was to determine if lost osseous support adjacent to root form implants could be regenerated using a guided tissue regeneration technique. Three fixtures were placed in each edentulous mandibular bicuspid region of two micro pigs. A total of 6 fixtures were placed in each pig. Due to the presence of a pathologic condition, which was in no way related to the research, the results of one pig were not evaluated. Following osseointegration, peri-implantitis were induced by the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 11 publications
2
51
0
1
Order By: Relevance
“…6 A variety of treatments have been tested in animal models for several years to evaluate their therapeutic potential for humans. For example, systemic antibiotics, 7,8 different implant surfaces, 9 and surgical techniques with bone-regeneration procedures [10][11][12][13][14] have been intensively tested in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…6 A variety of treatments have been tested in animal models for several years to evaluate their therapeutic potential for humans. For example, systemic antibiotics, 7,8 different implant surfaces, 9 and surgical techniques with bone-regeneration procedures [10][11][12][13][14] have been intensively tested in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…The role of submerged healing in peri-implantitis has not been solved clearly. Although Singh et al demonstrated in 1993 greater bone regeneration and re-osseointegration during submerged healing, Grunder et al found no differences between either healing method [103,104]. …”
Section: Reviewmentioning
confidence: 99%
“…60 Four more studies comparing different types of grafts, with or without membranes, reported bone fill and pocket depth reduction at periimplant defect when an air-powder abrasive instrument for 30 seconds either alone or with sodium carbonate solution. 65 However, only 35.6% of the total amount of bone fill in the peri-implant defect was osseointegrated, whereas the remaining 64.4% of the regenerated bone fill had a soft tissue interface between bone.…”
Section: Evidencementioning
confidence: 99%